Efficient light-driven particle capture actuator based on photo-thermal composite film
By using a fiber interference structure and a stacked design of graphene oxide/polydimethylsiloxane-gold nanobipyramidal composite film, the problems of low photothermal efficiency, unstable thermal field and complex preparation in photothermal driven particle manipulation are solved, realizing low power consumption, high efficiency particle capture and real-time sensing functions, which are suitable for the biomedical field.
Patent Information
- Application Number
- CN202511597452.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-04
- Publication Date
- 2026-01-30
Smart Images

Figure CN121423055A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of micro-nano manipulation technology, in particular to a graphene oxide (GO) / polydimethylsiloxane (PDMS)-gold nanobipyramid (AuNBPs) composite film-based optical-driven microparticle capture actuator and a preparation method thereof, which is suitable for precise manipulation of living cells, construction of micro-reactors and integration of microfluidic chips. BACKGROUND
[0002] Micro-particle manipulation technology has become a key bridge connecting micro-nano scale substances and macro applications due to its high flexibility and micro-structure, and has irreplaceable application value in the fields of biomedical manipulation (such as single cell sorting and organelle transport), microfluidic chips (such as micro-sample detection and micro-chemical reaction regulation), and nanomaterial assembly (such as ordered nano-structure construction). With the increasing demand for non-invasive, high-precision and low-power manipulation in the above fields, traditional manipulation methods based on mechanical contact and electromagnetic drive are gradually limited due to their defects such as easy damage to samples and complex structure. Optical driving manipulation technology has become a research hotspot in recent years due to its characteristics of no physical contact, environmental friendliness and fast response speed. Among them, the "indirect optical-driven capture technology" based on the photo-thermal effect is considered as an ideal solution for manipulation of living cells and sensitive biological tissues because it can avoid optical damage to biological samples caused by direct optical radiation.
[0003] Currently, the research of light-driven microparticle manipulation technology focuses on two directions: optimization of photothermal materials and design of driving structures. The existing light-driven microparticle manipulation still faces the following challenges: the contradiction between light-to-heat conversion efficiency and cost. The light-to-heat conversion efficiency of noble metal nanomaterials is strictly limited by the LSPR bandwidth, which cannot achieve wide-spectrum and high-efficiency absorption. While carbon-based materials, although lower in cost, require high concentration of doping to achieve ideal photothermal effect, which easily leads to material agglomeration and reduces efficiency. Meng Chun from Hefei University of Technology proposed a method of light-to-heat conversion, which realized 3D microparticle oscillator with fixed direction by laser heating on the surface of gold film, completely avoiding optical damage (Meng C, Lu F, Zhang N Q, et al. Optothermal Microparticle Oscillator Induced by Marangoni and Thermal Convection [J]. Langmuir, 2024, 40(14):8). The commonly used light-driven structure currently adopts an “open thermal field design”. In viscous media such as silicone oil and body fluid, the direction of heat conduction is difficult to constrain, leading to uneven temperature gradient distribution and easy drift, which in turn causes low microparticle capture efficiency. Li Fuwang from Guilin University of Electronic Technology proposed a new mechanism for truly non-contact manipulation through photothermal effect, which used laser self-assembly photothermal waveguide to generate non-isothermal temperature field and realized non-contact and non-destructive microparticle manipulation (Li, F., Wei, J., Qin, X. et al. Thermo-optical tweezers based on photothermal waveguides. Microsyst Nanoeng 10, 123 (2024)). The preparation of existing structures mostly depends on precise micro-nano processing equipment (such as electron beam lithography), which has a complicated process and poor repeatability. At the same time, most actuators only have the function of “capture”, lack the ability to monitor their own working state (such as temperature gradient size and whether the capture is stable), and cannot realize real-time regulation and parameter optimization of the capture process. Wei Zhan from Huazhong University of Science and Technology demonstrated a simple optical fiber microfluidic control device based on photothermal effect-induced convection, which can realize flexible manipulation and particle sorting in the range of hundreds of microns.(Zhan, Wei, M. Yang, and W. Song. "Optical fiber-based manipulation of microparticles in microfluidic channel through thermal convection." Applied Physics Express 12.12(2019):122004 (5pp)). Current photothermal-driven microparticle capture technologies still need to overcome technical bottlenecks related to "low power consumption, high stability, standardized preparation, and multifunctional integration" to meet the practical application needs in fields such as biomedicine.
[0004] This invention proposes a light-driven microparticle trapping actuator based on a GO / PDMS-AuNBPs composite film and its standardized fabrication method. By integrating the fiber optic FPI microcavity beam expander with the composite thin film's photothermal synergy, it solves the problems of low photothermal efficiency, high power dependence, and unstable thermal field in existing technologies. Furthermore, by clearly defining the process parameters for each fabrication step, batch-to-batch consistency of device performance is achieved, and real-time sensing functionality is integrated, broadening its application scenarios in the biomedical field. Summary of the Invention
[0005] To address the technical problems existing in the background art, the present invention provides a compact, highly integrated, and efficient optical particle capture actuator and its preparation method.
[0006] Preferably, the actuator comprises a fiber interference structure and a photothermal composite film as its core functional units, which can be directly integrated into micro-carriers such as microfluidic chips and bioreactors. The fiber interference structure is a support and light transmission carrier formed by fusing single-mode fiber (SMF) and hollow fiber (HCF), and the photothermal composite film is a stacked structure of graphene oxide (GO) film and polydimethylsiloxane (PDMS)-gold nanopyramidal (AuNBPs) film. These two components work synergistically to achieve particle capture at low power, and the fabrication process does not rely on precision micro / nano fabrication equipment, exhibiting high process repeatability.
[0007] This invention also provides a method for preparing the above-mentioned particle trapping actuator, comprising the following core steps:
[0008] S1, Fabrication of the fiber optic interference structure;
[0009] S1.1 SMF Cleaving: Standard single-mode fiber (such as Corning SMF-28e) is cleaved using a precision fiber cleaver to ensure that the fiber end face is flat and the perpendicularity error to the fiber axis is <0.5°, so as to avoid optical transmission loss due to uneven end face during subsequent fusion splicing.
[0010] S1.2 SMF and HCF fusion splicing: Select a 200 μm long hollow fiber (HCF, inner diameter 80 μm, outer diameter 125 μm) and use a commercial fiber fusion splicer (such as Fujikura FSM-60S) to splice it with the cut SMF.
[0011] S1.3 Fiber splice quality verification: The morphology of the fusion splice is observed using a high-resolution fiber optic microscope (1000× magnification) to confirm that there are no structural defects; the optical transmission loss is measured using an optical power meter (such as Agilent N7744A) until the loss requirement is met.
[0012] Preferably, in step S1.2, the welding parameters are set as follows: discharge current 15 mA and welding time 0.8 s, to ensure that there is no air gap or misalignment at the welding point.
[0013] Preferably, in step S1.3, the optical transmission loss needs to be less than 0.3dB.
[0014] S2. Preparation of photothermal composite thin films
[0015] Preparation of S2.1 GO thin films;
[0016] S2.1.1 Dispersion preparation: 20 wt% GO powder was dispersed in deionized water and ultrasonicated for 30 min using an ultrasonic instrument with a power of 300 W and a frequency of 40 kHz to ensure that the GO sheets were uniformly dispersed (particle size distribution 100~200 nm) and there was no obvious agglomeration.
[0017] S2.1.2 Liquid film formation: The SMF-HCF structure prepared in S1 is fixed on a three-dimensional micro-displacement platform (accuracy 1 μm). The platform is adjusted so that the end face of HCF away from SMF is vertically downward and slowly lowered until it picks up 2 μL of the above GO dispersion. A uniform liquid film is formed on the end face of HCF by utilizing the surface tension of the liquid.
[0018] S2.1.3 Drying and curing: The SMF-HCF structure with the GO liquid film was transferred to a vacuum oven and dried at 50°C for 1 h to remove residual solvent, finally forming a GO film with a thickness of 50~100 nm. The thickness and flatness of the film were characterized by atomic force microscopy (AFM) to ensure that the film was free of cracks and peeling.
[0019] S2.2 Preparation of PDMS-AuNBPs thin films;
[0020] S2.2.1 Synthesis of AuNBPs: AuNBPs were synthesized using a seed-mediated growth method. Specifically, 10 mL of 0.01 M chloroauric acid (HAuCl4) solution and 10 mL of 0.01 M sodium citrate solution were mixed and heated in a water bath at 60°C for 30 min to prepare a gold seed solution. Then, 50 mL of 0.01 M HAuCl4 solution, 5 mL of 0.01 M sodium citrate solution, and 2 mL of 0.01 M silver nitrate solution were mixed, and 1 mL of the gold seed solution was added. The mixture was then reacted in a water bath at 60°C for 2 h. The localized surface plasmon resonance (LSPR) peak of the AuNBPs was monitored using a UV-Vis spectrophotometer (such as a Shimadzu UV-2600) to ensure that it was located at 980 nm.
[0021] S2.2.2 Preparation of the mixture: The synthesized AuNBPs solution is mixed with PDMS prepolymer (such as Dow Corning Sylgard 184) at a mass ratio of 1:10 and magnetically stirred for 30 min; PDMS curing agent (prepolymer to curing agent mass ratio of 10:1) is added and stirring is continued for 15 min until the mixture is homogeneous, followed by vacuum degassing for 5 min to remove air bubbles from the mixture;
[0022] S2.2.3 Coating and Crosslinking: Using a micropipette, 1 μL of the above PDMS-AuNBPs mixture was dropped onto the GO membrane surface of the HCF end face, ensuring that the mixture completely covered the GO membrane (covering a diameter of approximately 125 μm); the structure was placed in an 80℃ oven for 2 h to cure, allowing the PDMS to fully crosslink and form a PDMS-AuNBPs membrane with a thickness of 150~250 nm; the cross-section of the membrane was observed by scanning electron microscopy (SEM) to confirm that the GO membrane and the PDMS-AuNBPs membrane were tightly bonded and without gaps.
[0023] Furthermore, the trapping actuator comprises a fiber optic interference structure and a photothermal composite thin film as its core functional components. These two elements work synergistically to achieve particle trapping at low power, and the fabrication process does not rely on precision micro / nano fabrication equipment, exhibiting high process repeatability.
[0024] The technical solution provided by this invention has the following beneficial effects: The proposed solution clearly defines the process parameters for each preparation step (such as welding current, ultrasonic time, and curing temperature), eliminating the need for precision equipment like electron beam lithography and enabling large-scale production. It is compatible with various liquid environments, including silicone oil and cell culture media, and can be integrated into micro-carriers such as microfluidic chips and bioreactors, covering multiple fields including biomedicine, microchemical engineering, and nanomaterial assembly. Furthermore, particle capture requires only a minimum of 11.9 mW of laser light, avoiding thermal damage to biological samples from high-power lasers and meeting the manipulation requirements of sensitive samples such as living cells. The particle capture efficiency is ≥95%, and it is adaptable to particles of different sizes from 5 to 400 μm, making it suitable for a wide range of applications. Attached Figure Description
[0025] Figure 1 This is a schematic diagram of a photoelectric particle capture actuator proposed in this invention.
[0026] Figure 2 This is a schematic diagram of the preparation process of a composite thin film made from a photothermal material according to the present invention.
[0027] Figure 3 This is a schematic diagram of the temperature field simulation results proposed in this invention.
[0028] Figure 4 This is a schematic diagram illustrating the structure and principle of one embodiment of the optical drive particle capture actuator described in this invention. Detailed Implementation
[0029] To make the technical solutions and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only for explaining the present invention and are not intended to limit the present invention. The accompanying drawings are for illustrative purposes only, representing schematic diagrams only, not actual physical images, and should not be construed as limiting the present invention.
[0030] like Figures 1 to 4 As shown, Figure 1 This is a schematic diagram of a light-driven particle trapping actuator proposed in this invention. Figure 2 This is a schematic diagram illustrating the preparation process of a composite thin film made from a photothermal material according to the present invention. Figure 3 This is a schematic diagram of the temperature field simulation results proposed in this invention. Figure 4 This is a schematic diagram illustrating the structure and principle of one embodiment of the optical drive particle capture actuator described in this invention.
[0031] Reference Figure 4 The present invention discloses a photoelectric particle trapping actuator for precise drug delivery, comprising the following steps:
[0032] S1. Fabrication of fiber optic interference structures;
[0033] S1.1 SMF Cutting and Pre-treatment: The specific operating steps are as follows: Take a 20cm length of SMF, peel off 2cm of the coating layer, wipe the fiber surface with anhydrous ethanol until there are no impurities; use a Fujikura CT-30 precision cleaver to cut one end of the SMF, set the cutting angle to 90°, and observe the cut end face under a fiber optic microscope to ensure that the end face is flat and free of cracks;
[0034] S1.2 SMF and HCF Fusion Splicing: Fix the diced SMF and HCF onto the two clamps of the Fujikura FSM-60S fiber optic fusion splicer, respectively. Adjust the clamp positions to align the axes of the two fibers (coaxiality error < 1 μm). Set the fusion parameters: discharge current 15 mA, discharge time 0.8 s, pre-discharge intensity 50%, and start the fusion program. After fusion, observe the fusion joint using the fusion splicer's built-in imaging system to ensure there are no air gaps, misalignments, or over-fusion. Preferably, the HCF cut length is 200 μm (measured with a high-precision vernier caliper, error ± 5 μm).
[0035] S2. Preparation of photothermal composite thin films;
[0036] Preparation of S2.1 GO thin film: The fiber interference structure (SMF-HCF) prepared in S1 was fixed on a three-dimensional micro-displacement platform (accuracy 1 μm). The platform was adjusted so that the end face of HCF away from SMF was vertically downward. 2 μL of GO dispersion was taken with a 10 μL micropipette and dropped onto a glass slide that had been plasma-cleaned (power 50 W, time 10 min). The micro-displacement platform was slowly lowered so that the end face of HCF contacted the surface of the dispersion, and a uniform liquid film was formed on the end face using the surface tension of the liquid. The structure with the liquid film was then transferred to a vacuum oven and dried at 50 °C for 1 h to remove moisture. After drying, the thickness of the GO film was characterized by AFM, which needed to be controlled within 50~100 nm, and the film surface roughness Ra < 5 nm.
[0037] S2.2 Preparation of PDMS-AuNBPs thin films;
[0038] S2.2.1 Preparation of the mixture: Preferably, the mass ratio of PDMS prepolymer to curing agent is 10:1; take 1g of PDMS prepolymer and pour it into a centrifuge tube, add 0.1g of the above AuNBPs solution (concentration 0.1mg / mL), and stir with a vortex mixer (3000rpm) for 30min; then add 0.1g of PDMS curing agent, and continue stirring for 15min until the mixture is uniform; place the centrifuge tube in a vacuum drying oven for 5min to remove air bubbles from the mixture (to avoid pores in the coated film).
[0039] S2.2.2 Coating and Crosslinking Curing: Use a 1μL micropipette to draw up the mixture and slowly drop it onto the GO film surface of the HCF end face (ensure that the mixture completely covers the GO film without any omissions); place the structure in an 80℃ constant temperature oven and cure for 2 hours (insufficient curing time will result in incomplete crosslinking of PDMS, while excessive curing time may lead to embrittlement of the film layer); at this point, the actuator preparation is complete.
[0040] S3. Integration and Testing;
[0041] Specifically, the actuator is embedded in a custom microfluidic chip (microchannel size 1mm × 200μm), and the channel is filled with silicone oil of 99.5% purity; polystyrene microspheres (5~400μm in diameter) or microbubbles (150~250μm in diameter) are added to the silicone oil at a concentration of 1×10⁻⁶. 4 The particle count was measured per mL. A Thorlabs L980P100 980nm laser light source (power adjustable from 0 to 200mW) was used. The initial distance between the actuator and the particles was adjusted by a three-dimensional micro-displacement platform (fixed at 300μm). The capture process was recorded using an Olympus IX73 microscope (magnification 200×) and a high-speed camera (frame rate 30fps).
[0042] The optical particle capture actuator designed in this embodiment, through precise control of material ratio and processing parameters, shows that the present invention is significantly superior to traditional technologies in terms of low power consumption, capture efficiency, stability, biocompatibility, and cost control. At the same time, the preparation process of the present invention does not rely on precision equipment such as electron beam lithography, which can meet the needs of large-scale production.
[0043] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical methods and inventive concepts of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A high-efficiency light-driven microparticle capturing actuator based on a photo-thermal composite film, characterized in that, It comprises: Optical thermal composite film (1), optical fiber interference microcavity structure (2); the optical fiber interference structure is formed by fusing single-mode optical fiber SMF (3) and hollow optical fiber HCF (4), and the optical thermal composite film is coated on the end face of the HCF away from the SMF, and the optical thermal composite film and the optical fiber interference structure jointly form a Fabry-Perot interference (FPI) microcavity; the sensing unit realizes real-time state monitoring of the particle capture process by monitoring the reflection spectrum change of the FPI microcavity.
2. The high-efficiency light-driven particle capturing actuator of claim 1, wherein, The optical thermal composite film comprises a GO film and a PDMS-AuNBPs film which are sequentially laminated; the GO film is a light-heat conversion functional layer, the thickness is 50-100 nm, and the light absorption efficiency under 980 nm wavelength is not less than 85%; the PDMS-AuNBPs film is a structure support and auxiliary light-heat layer, the mass ratio of PDMS to curing agent is 10:1, the mass ratio of AuNBPs to PDMS is 1:100, the local surface plasmon resonance (LSPR) peak of AuNBPs is located near 980 nm, and the thermal conductivity of PDMS is 0.18 W / m·K.
3. A method of making an optical-driven microparticle trapping actuator as claimed in any one of claims 1-2, characterized by, It comprises the following steps: S1, preparing an optical fiber F-P interference structure: (1) cutting SMF by using a precision optical fiber cutting knife to ensure that the end face is flat and the perpendicularity error with the SMF axis is less than 0.5°; (2) using a commercial optical fiber fusion machine to fuse SMF and HCF, setting the fusion parameters as discharge current 15 mA and fusion time 0.8 s; (3) after fusion, observing by a high-resolution optical fiber microscope to ensure that there is no air gap or misplacement, and measuring the optical transmission loss by an optical power meter to be less than 0.3 dB; S2, preparing a GO film: (1) taking 20wt% GO powder dispersed in deionized water, using an ultrasonic instrument with a power of 300 W and a frequency of 40 kHz to ultrasonic treat for 30 min, until the GO plate layer is uniformly dispersed and there is no obvious agglomeration; (2) fixing the fused SMF-HCF structure on a three-dimensional micro-displacement platform, adjusting the platform to make the HCF end face vertical downward, slowly lowering to dip 2 μL of the above GO dispersion liquid, and using the liquid surface tension to form a uniform liquid film on the HCF end face; (3) transferring the structure with GO liquid film to a vacuum oven with a temperature of 50℃ for drying for 1 h, and forming a GO film with a thickness of 50-100 nm after removing the residual solvent; S3, preparing a PDMS-AuNBPs film: (1) AuNBPs were synthesized by seed-mediated growth method: ①10 mL 0.01M HAuCl4 solution and 10 mL 0.01M Na3C6H5O7 solution were mixed and heated at 60℃ for 30 min to prepare gold seed solution; ② 50 mL 0.01M HAuCl4 solution, 5 mL 0.01M Na3C6H5O7 solution and 2 mL 0.01M AgNO3 solution were mixed, 1 mL gold seed solution was added, and the mixture was reacted at 60℃ for 2 h. The LSPR peak was located at 980 nm by UV-Vis spectrophotometer; (2) The synthesized AuNBPs solution was mixed with PDMS prepolymer at a mass ratio of 1:10, stirred for 30 min, and then PDMS curing agent was added (prepolymer to curing agent mass ratio of 10:1), and the mixture was stirred for another 15 min to remove air bubbles; (3) 1 μL of the above PDMS-AuNBPs mixture was taken by a micropipette and dropped on the GO film surface of the HCF end face to cover the entire GO film; (4) The structure after dropping was placed in an 80℃ oven for 2 h to completely crosslink the PDMS and form a PDMS-AuNBPs film with a thickness of 150-250 nm.
4. The optical-driven particle capture actuator of claim 1, wherein, The FPI microcavity was composed of HCF, GO film and PDMS-AuNBPs film, and the cavity length was 150-200 μm. Under the excitation of 5.2 mW 980 nm laser, the GO film could realize local temperature rise of 45℃.
5. The optical-driven particle capture actuator of claim 1, wherein, The driving mechanism of particle trapping is that the temperature gradient generated by the photo-thermal composite film induces the surface tension gradient of the surrounding silicone oil, and then generates Marangoni force (F M ), F M direction points to the end face of the HCF and is much larger than the thermophoretic force (F T ), which drives the particles to move to the end face of the HCF and is trapped; the Marangoni force F M is calculated according to the formula F M =2πR・(dσ / dT)・ΔT, wherein R is the particle radius, dσ / dT is the temperature derivative of the surface tension of the silicone oil (-0.1×10⁻³ Nm⁻¹K⁻¹), and ΔT is the temperature gradient.
6. The optical-driven particle capture actuator of claim 1, wherein, The monitoring method of the sensing unit included: using a 900-1700 nm broadband light source to irradiate the SMF, and collecting the reflection spectrum of the FPI microcavity by a spectrometer; the increase of laser power led to the increase of microcavity length, and the reflection spectrum was red-shifted. The resonance wavelength fluctuation was less than ±0.27 nm at 35℃, and the temperature gradient could be judged in real time by the amount of red shift.
7. The optical-driven microparticle capture actuator of any one of claims 1-6, wherein, The diameter range of the captured particles was 5-400 μm. The minimum laser excitation power required to capture a 130 μm particle was 11.9 mW, and the time required to capture a 50 μm particle under 18.6 mW laser power was 6 s. The materials GO and PDMS used in the preparation process had good biocompatibility, and the cell survival rate was ≥95% in the living cell manipulation experiment.